Tetracycline‐levofloxacin versus amoxicillin‐levofloxacin quadruple therapies in the second‐line treatment of Helicobacter pylori infection. Issue 5 (12th August 2021) - Hsu, Ping‐I; Tsay, Feng‐Woei; Kao, John Y.; Peng, Nan‐Jing; Chen, Yan‐Hua; Tang, Sheng‐Yeh; Kuo, Chao‐Hung; Kao, Sung‐Shuo; Wang, Huay‐Min; Wu, I‐Ting; Shie, Chang‐Bih; Chuah, Seng‐Kee; et al.
Abstract: Background: The Maastricht V/Florence Consensus Report recommends amoxicillin‐fluoroquinolone triple or quadruple therapy as a second‐line treatment for Helicobacter pylori infection. An important caveat of amoxicillin‐fluoroquinolone rescue therapy is poor eradication efficacy in the presence of fluoroquinolone resistance. The study aimed to investigate the efficacies of tetracycline‐levofloxacin (TL) quadruple therapy and amoxicillin‐levofloxacin (AL) quadruple therapy in the second‐line treatment of H .  pylori infection. Methods: Consecutive H . pylori ‐infected subjects after the failure of first‐line therapies were randomly allocated to receive either TL quadruple therapy (tetracycline 500 mg QID, levofloxacin 500 mg QD, esomeprazole 40 mg BID, and tripotassium dicitrato bismuthate 300 mg QID) or AL quadruple therapy (amoxicillin 500 mg QID, levofloxacin 500 mg QD, esomeprazole 40 mg BID, and tripotassium dicitrato bismuthate 300 mg QID) for 10 days. Post‐treatment H .  pylori status was assessed 6 weeks after the end of therapy. Results: The study was early terminated after an interim analysis. In the TL quadruple group, 50 out of 56 patients (89.3%) had successful eradication of H .  pylori infection. Cure of H .  pylori infection was achieved only in 39 of 52 patients (69.6%) receiving AL quadruple therapy. Intention‐to‐treat analysis showed that TL quadruple therapy achieved a markedly higher eradication rate than AL quadruple therapy (95% confidence interval: 4.8% to 34.6%; p  = 0.010). Further analysis revealed that TL quadruple therapy had a high eradication rate for both levofloxacin‐susceptible and resistant strains (100% and 88.9%). In contrast, AL quadruple therapy yielded a high eradication for levofloxacin‐susceptible strains (90.9%) but a poor eradication efficacy for levofloxacin‐resistant strains (50.0%). The two therapies exhibited comparable frequencies of adverse events (37.5% vs 21.4%) and drug adherence (98.2% vs 94.6%). Conclusions: Ten‐day TL quadruple therapy is more effective than AL quadruple therapy in the second‐line treatment of H . pylori infection in a population with high levofloxacin resistance.